2023
DOI: 10.1177/02692155231157301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a telephone and web-based problem-solving intervention for stroke caregivers on stroke patient activities of daily living: A randomized controlled trial

Abstract: Objective To test for effects of a problem-solving intervention for stroke caregivers on stroke survivor activities of daily living. Design Two-arm parallel randomized clinical trial with repeated measures at 11 weeks and 19 weeks. Setting Medical centers for US military Veterans. Subjects Caregivers of stroke survivors. Intervention A registered nurse guided caregivers in using problem-solving strategies emphasizing creative thinking, optimism, planning, and expert information to address challenges associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
24

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(49 citation statements)
references
References 45 publications
0
25
0
24
Order By: Relevance
“…When analyzing the information of the articles, in relation to the year of publication, it was identified that it covered between 2006 and 2020. Moreover, four studies were carried out in the United States (44%) (26)(27)(28)(29) two in Brazil (22%) (30,31) and one in China, the United Kingdom and Egypt (11%) (17,32,33) , respectively. Likewise, 88.8% of studies were articles (17,(26)(27)(28)(29)(31)(32)(33) and 11.1% were a thesis (30) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…When analyzing the information of the articles, in relation to the year of publication, it was identified that it covered between 2006 and 2020. Moreover, four studies were carried out in the United States (44%) (26)(27)(28)(29) two in Brazil (22%) (30,31) and one in China, the United Kingdom and Egypt (11%) (17,32,33) , respectively. Likewise, 88.8% of studies were articles (17,(26)(27)(28)(29)(31)(32)(33) and 11.1% were a thesis (30) .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, four studies were carried out in the United States (44%) (26)(27)(28)(29) two in Brazil (22%) (30,31) and one in China, the United Kingdom and Egypt (11%) (17,32,33) , respectively. Likewise, 88.8% of studies were articles (17,(26)(27)(28)(29)(31)(32)(33) and 11.1% were a thesis (30) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations